Feasibility Study of Clinical Psychopragmatic from Philosophical Point of View in Student Creative Writing - Purwati Anggraini; Suyatno Suyatno; Tengsoe Tjahjono (International Journal of Educational Narratives, 2024)
Background. The issue in literary appreciation writing for UMM students of Indonesian Language Education needs an appropriate response. There are two causes Involved: technical and psychological Issues. Purpose. Despite adequate writing knowledge and skill, they experience challenges in writing literary appreciation. Method. Thus, it requires a comprehensive reconstruction of a new theory of clinical psycho-pragmatism, originating from psycholinguistics and clinical pragmatics, to address the issue. Results. The clinical psychopragmatic theory can be helpful as a research approach and potentially be the base of a new theory through knowledge reconstruction comprising ontologism, axiology, and epistemology. Conclusion. Thus, this theory, as a transdisciplinary theory, is more specific compared to a combination of psycholinguistics and clinical pragmatics.